A study on knowledge and practice of OCP among Young adolescent girls- A cross sectional hospital based study (The Planet, 2022)
Introduction: Adolescents account for almost one-fourth (23%) of the Bangladeshi population. The government has designated adolescent health as a priority concern in the Health, Nutrition, and Population Sector Program (HNPSP), yet access to reproductive health information and services is extremely restricted. The current study focused on 98 teenagers' health seeking behaviors and reproductive knowledge, with a particular emphasis on contraceptive information. Aim of the study: The aim of the study was to understand the knowledge and practice of oral contraceptive pills among adolescent girls who visited the study hospital. Methods: This cross-sectional descriptive study was conducted at the Department of Obstetrics Gynecology, Institute of child and Mother Health, Matuail, Bangladesh. The study duration was 6 months, from July 2007 to December 2007. Result: The study was conducted with a total of 98 adolescent females, where mean age was 15.95 years, and majority (68.4%) were unmarried. Lower abdominal pain was the most common problem, followed by menstrual problems. Knowledge regarding health clinic came mostly from family or relatives. Very few had a history of OCP usage, and although the basic knowledge of contraceptives was high among the adolescent females, practice rate was relatively low. Majority of the participants had received knowledge regarding contraceptives primarily from friends and newspapers. Conclusion: The study observed that even amongmarried participants, use of OCP is very small. Although many adolescents know about contraceptives, the knowledge is not available to the whole adolescent population as it should be. Even among those who know about contraceptives, most of their knowledge comes from friends and newspapers, instead of medical programs of professionals.
Keywords: Reproductive; Adolescents; Contraceptives; OCD